Collective behaviour in cascade model depends on turn of the choice. (2016) - Iwanaga, Saori; Namatame, Akira
There are growing interests for studying collective behaviour including the dynamics of markets, the emergence of social norms and conventions, and collective phenomena in daily life such as traffic congestion. In cascade model, collective behaviour is affected in the structure of the social network and threshold to make decision, and the collective behaviour was stochastic, similar to threshold model in local interaction. In both model, although decisions of agents are deterministic, collective behaviour of population become stochastic. In previous work, we analysed origin of stochastic collective behaviour and we found that collective behaviour depends on the initial behaviour of high degree in threshold model in local interaction. In this paper, we analysed origin of stochastic collective behaviour in cascade model. We analysed why collective behaviour is stochastic in scale free network. Then, we show that turn of the choice effects on collective behaviour not the first choices.